Antimicrobial and Anticancer Application of Silver(I) Dipeptide Complexes - Gabriela Kuzderová (MDPI AG, 2021)
Three silver(I) dipeptide complexes [Ag(GlyGly)]n(NO3)n (AgGlyGly), [Ag2(GlyAla)(NO3)2]n (AgGlyAla) and [Ag2(HGlyAsp)(NO3)]n (AgGlyAsp) were prepared, investigated and characterized by vibrational spectroscopy (mid-IR), elemental and thermogravimetric analysis and mass spectrometry. For AgGlyGly, X-ray crystallography was also performed. Their stability in biological testing media was verified by time-dependent NMR measurements. Their in vitro antimicrobial activity was evaluated against selected pathogenic microorganisms. Moreover, the influence of silver(I) dipeptide complexes on microbial film formation was described. Further, the cytotoxicity of the complexes against selected cancer cells (BLM, MDA-MB-231, HeLa, HCT116, MCF-7 and Jurkat) and fibroblasts (BJ-5ta) using a colorimetric MTS assay was tested, and the selectivity index (SI) was identified. The mechanism of action of Ag(I) dipeptide complexes was elucidated and discussed by the study in terms of their binding affinity toward the CT DNA, the ability to cleave the DNA and the ability to influence numbers of cells within each cell cycle phase. The new silver(I) dipeptide complexes are able to bind into DNA by noncovalent interaction, and the topoisomerase I inhibition study showed that the studied complexes inhibit its activity at a concentration of 15 μM.